PENGARUH POLA MONITORING MENYIKAT GIGI TERHADAP PENINGKATAN KEBERSIHAN GIGI & MULUT MURID SDN 2 SELAT KECAMATAN SUSUT BANGLI - Ni Ketut Ratmini; I Made Budi Artawa; I Nyoman Gejir (Jurusan Keperawatan Gigi Poltekkes kemenkes Denpasar, 2018)
Basic Health Research Result (Hasil Riset Kesehatan Dasar/Riskesdas) in 2007 reported that the prevalence of the Indonesian population has dental health problem at 23,4%. Bangli Regency has the lowest proportion in term of handling treatment, dental fillings and dental extraction and is recorded to be the second top in the prevalence of dental and oral health as well as known to have 61,8% of the population with caries experience (Depkes RI., 2008). The optimal community dental health status kesehatan gigi masyarakat can be achieved by improving the promotive and preventive efforts early until elderly age (Depkes RI, 1999). The efforts in improving children’s dental and oral hygiene is by the involvement of parents in dental health education which can be done by: 1) motivating through tooth brushing; 2) determining the frequency id tooth brushing which is twice a day; 3) encouraging better cooperation between children and the mothers as the coaches in tooth brushing; 4) motivating children to behave positively towards tooth brushing efforts; 5) chidren are given motivation to be diligent in brushing teeth under the coach of the mothers (Howard, 1969 dalam Budiharto, 2009).The objective of this study is to know the monitoring pattern of tooth brushing towards the improvement of dental and oral hygiene among school students of SDN 2 SelatKecamatan Susut Kabupaten Bangli in 2016.The design of this study is pretest-postest control group disign, which is conducted in SDN 2 Selat Kecmatan Susut Kabupaten Bangli in 2016. The population of this study is all students of sekolah dasar negeri (SDN) 2 Selat Kecamatan Susut Kabupaten Bangli and the samples of the study are taken randomly (randoom sampling) The finding of this study is that the monitoring pattern of brushing teeth significantly influences the dental and oral hygiene of students of sekolah dasar negeri 2 Selat, Kecamatan Susut, Kabupaten Bangli in 2016.